A Stereoselective Total Synthesis of Decarestrictine I. Issue 6 (June 2014) - Yadav, Jhillu Singh; Venkatesh, Miriyal; Kumar, Alleni Suman; Reddy, Poli Adi Narayana; Reddy, Basi V. Subba; Prasad, Attaluri R.
Abstract A convergent and stereoselective total synthesis of decarestrictine I, a polyketide natural product, is described. Both acid and alcohol fragments were prepared from the readily available L‐malic acid via StillGennari olefination and Sharpless asymmetric epoxidation. The Steglich esterification and ring‐closing metathesis (RCM) are employed to combine both acid and alcohol fragments.